Parentheticals - Dehé, Nicole; Kavalova, Yordanka (Linguistik aktuell, 2007)
Parentheticals are a fascinating way of interrupting spoken and written utterances. This paper focuses on prosodic aspects of the analysis of such constructions in contemporary German. The investigation starts with a discussion of the prosodic features relevant to the study of parentheticals such as discussed in previous literature - intensity, articulation rate, fundamental frequency, pauses, and intonation contours - and, drawing on these features, goes on to discuss data from recent parliamentary debates. The results show that future prosodic studies should focus on the transition zone betw.